The Iranian –Sudanes Relations (1985-1989) Historical Study (Journal of the College of Education for Women, 2019)
The Iranian-Sudanese relations during the era of the transitional government (1985-1986), and the era of the third democratic government, has seen a marked improvement, particularly since the transitional government, which was formed in Sudan following a popular uprising that toppled former President Jaafar Nimeiri followed based on balancing policy in international relations, which is the same policy adopted by the government of Sadiq al-Mahdi that, especially that Mr. Sadiq al-Mahdi had enjoyed close ties with the government in Tehran before he took office, and on the basis of the policy of diplomatic representation between the two countries returned since the time of the transitional government after relations were severed due to the policy former President Jaafar Nimeiri.- The Iranian policy focused after the Islamic revolution in February 1979 on the export of the revolution to the Arab and Islamic countries, since Sudan is one of the most Islamic countries in which the factors helping to spread the revolution are available, particularly in Islamic circles, so Iran has sought to document the relationship with the National Islamic Front and extended money and weapons to succeed in achieving an Islamic revolutionary society in Sudan.The Iranian political system sought to make Sudan a base from which to set off towards the Arab and African countries in order to establish the rule of similar systems in those countries.- Despite the close ties that the government of Sudan have linked the government in Tehran, but the Sudanese government has worked to put an end to Iranian meddling in the internal affairs of Sudan, and it turned out that by rejecting Iran's offer of financial and military aid to Sudan to eliminate the rebel movement, led by John Garang in southern Sudan.- It turns out the improvement of relations between the two countries through the exchange of official visits at the highest levels and contract agreements in all fields, and the feet of Iran to provide economic aid to Sudan.